Safety in the civil construction sector: Standards and preventive measures (Research, Society and Development, 2023)
Currently, in Brazil, the construction industry is one of the economic sectors with the highest labor utilization, consequently, it is the sector with the highest rate of occupational accidents. The Federal Constitution mandates that workers are entitled to protection of their health, physical and moral integrity, and safety in the execution of their activities. Work should be performed under conditions that contribute to the improvement of quality of life and personal and social fulfillment. Worker safety and health are the responsibility of both the employer and the professionals involved in the workplace environment. Therefore, specific Regulatory Norms have been established for enhanced worker safety.